Shifting his weight from foot to foot : between autobiography and autofiction in the poetry of Paul Muldoon - Tauvry, Alexandra (Trinity College (Dublin, Ireland). School of English, 2014)
In his review of Maggot (2010), published in The New York Times Book Review, Richard Eder writes that ‘Paul Muldoon is a shape-shifting Proteus to readers who try to pin him down’ (n. pag.). Muldoon’s poetic persona is, in fact, often evasive, unpredictable, and polymorphous, since the poet constantly navigates between the real and the fictional. This thesis examines Muldoon’s poetic first- person voice in light of the concepts of autobiography and autofiction. My intent is not to put his poetry within specific theoretical strangleholds, but rather argue that theories of autobiographical poetry and of autofiction may open up new ways of reading his work and understanding the poetic ‘I’. This thesis argues that, although Muldoon weaves unmediated autobiographical elements into his writing, he also creates a strategically fictional first-person voice in order to blur the frontiers between authenticity and artfulness.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin